Pengaruh Tipe Infill dan Temperatur Nozzle terhadap Kekuatan Tarik Produk 3D Printing Filamen Pla+ Esun - Z. S. Suzen; Hasdiansah; Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2020)
The increasing technology of the manufacturing industry now makes the industry competition, especially in the field of manufacturing increasingly stringent in developing products with accurate dimensions. The process of getting accurate and precise dimension results is very important in improving the quality of a product to be made. With the development of this technology, the manufacturing industry has begun to develop products with the method of adding materials known as rapid prototyping or layer manufacturing, one of which is technology using 3D printing machines. This research was carried out on a PRUSA 3D Printing FDM model with dimensions of 220 mm x 220 mm x 250 mm and using a nozzle measuring 0.4 mm. The material used is a PLA + filament with a diameter of 1.75 mm with variations in the nozzle temperature parameters (205 ° C, 215 ° C, 225 ° C), layer thickness 0.2, bed temperature 60 ° C, travel speed 100, printing speed 50 , infill type (Grid, Lines, Triangles, Tri Hexagon, Cubic, Cubic Subdivision, Octet, Quarter Qubic, Concentric, Zig Zag, Cross, Cross 3D, Gyroid) which will be determined in Ultimaker Cura 4.4.0 software, resulting in 39 printed sample. The results obtained after testing the highest tensile strength values are found in the 22nd test specimen that is 43.20 MPa with 215 nozzle temperature parameters and Infill Type Concentric, while the lowest tensile strength values are found in the 22nd test specimen which is 24.50 MPa with nozzle temperature parameters 205 ° C and Infill Type Cross.